Assessment Through Student Portfolios in Omani Schools - Al-Amri, Khalid Ali (2006)
A Master of Arts thesis in Teaching English to Speakers of Other Languages by Khalid Ali Al-Amri Entitled, "Assessment Through Student Portfolios in Omani Schools," June 2006. Thesis Advisor is Dr. Rodney Tyson. Available are Both Soft and Hard Copies of the Thesis.